Wellness, Emotion Regulation, and Relapse During Substance Use Disorder Treatment. (2nd January 2020) - Clarke, Philip B.; Lewis, Todd F.; Myers, Jane E.; Henson, Robert A.; Hill, Brent
Abstract : Using a cross‐sectional study design, the authors investigated the impact of wellness and emotion regulation on relapse in 179 individuals currently enrolled in substance use disorder treatment. An integration of the indivisible self model of wellness (Myers & Sweeney, 2004) and the covert antecedents model of relapse (Marlatt, 1985) informed the study hypothesis that emotion regulation mediates the wellness‐relapse relationship. Binomial logistic regressions revealed that Creative Self wellness (odds ratio [OR] = 1.09, p = .002), reappraisal (OR = 1.08, p = .008), difficulties in emotion regulation (OR = 1.03, p = .007), and Physical Self wellness (OR = 0.95, p < .001) were associated with the odds of relapse on any given day during treatment. Sobel tests indicated 2 occurrences of full mediation, including that difficulties in emotion regulation mediated the relationship between Coping Self wellness and relapse (OR = 0.97, p = .015).